Trophic relationships of a subtidal fish assemblage in the Francisco Coloane Coastal Marine Protected Area, southern Chilean Patagonia - Hune, Mathias; Davis, Ernesto; Murcia, Silvia; Gutierrez, David; Haro, Daniela (My University, 2018)
A combination of stomach content and nitrogen (delta N-15) and carbon (delta C-13) stable-isotope analysis was used to assess the trophic interactions and feeding habits of three notothenioid coastal fish (Champsocephalus esox, Patagonotothen tessellata and Patagonotothen cornucola) and one exotic salmon species (Oncorhynchus tschawytscha) with diverse life habits (benthic and benthopelagic) in the Francisco Coloane Coastal Marine Protected Area, southern Chile. The stomach contents of C. esox were mainly fish; those of P. cornucola and O. tschawytscha were crustacean decapods, Munida gregaria. A cluster analysis on isotope data and stable-isotope Bayesian ellipses detected two different predator groups, one with benthopelagic habits (C. esox and O. tshawytscha) and one with benthic habits (P. cornucola and P. tessellata). These results were supported with similar isotopic trophic level of each group. We suggest that the exotic salmon O. tschawytscha is a generalist predator with a broad trophic niche that may compete with the native notothenioid C. esox, as both have equivalent trophic levels with substantial overlap. This preliminary study is the first on trophic relationships of a subtidal fish assemblage within a remote ecosystem of fjords and channels in Chile's southern Patagonia.
Keywords: notothenioidei; exotic salmonid; trophic level; feeding habits; magellan region; sub-antarctic